A case of ectopic salivary gland of the larynx. Issue 3 (June 2018) - Tajima, Shori; Yamauchi, Kouichi; Higo, Ryuzaburo; Ikeda, Katsuhisa
Abstract: A 46-year-old man presented with sore throat. Laryngoscopic findings revealed a smooth yellow mass occupying the anterior portion of the false vocal fold on the left side. The authors performed biopsy under general anesthesia. The histopathological diagnosis was ectopic salivary gland. Because salivary glands are usually not found under the false vocal fold mucosa, ectopic salivary gland of the larynx was diagnosed. It is necessary to consider the possibility of ectopic salivary gland for mass lesions if swelling of the provisional vocal cord is found.